Systematization of risk factors of maladjustment states formation in students under modern conditions - Khaustov, Maksim (ScienceRise: Medical Science, 2017)
Aim of the work: To systematize pathogenetically important factors of adaptation disorders in students of the medical university. Materials and methods of research: the complex examination of 412 students of І–ІІІ years of Kharkov national medical university, 17–22 years old, was realized, observing principles of bioethics and deontology. All examined persons were divided in three groups:1 group – 215 of students-dwellers of the Eastern Ukraine; 2 group – 87 students-dwellers of Lugansk and Donetsk regions, who entered Kharkov national medical university before the beginning of ATO; 3 group – 110 students-migrants from ATO zone. Research methods: clinical-anamnestic, psychodiagnostic, statistical. Results. The research results demonstrated that students-migrants express the higher level of adaptation disorders compared with ones of І and ІІ groups. Students relate to factors that influence adaptation complications: life stereotype change, difficult learning material, severe learning discipline, necessity to work out missed activities and lectures. The stress factors for students-migrants are a necessity to adapt in the new collective, abrupt change of the life stereotype, new social status - constrainedly migrated persons. Expressed manifestations of anxiety and depression are typical for patients with adaptation disorders (in overwhelming majority students of ІІІ group). It was established, that deviations of scales of depression, hypochondria, hysteria, psychopathy, psychasthenia are typical for personal profiles of women with maladjustment signs. Men with adaptation disorders most often demonstrate deviations of scales of hypochondria, depression, hypomania, schizophrenia. Conclusions. Students relate to factors that influence adaptation complications: life stereotype change, difficult learning material, difficult terminology, necessity to work out missed activities and lectures. The risk factors of adaptation disorders formation for students-migrants are a necessity to adapt in the new collective, abrupt change of the life stereotype, new social status – CMP; high indices of anxiety and depression; prevalence of psychopathic, hysterical and depressive features